2023
DOI: 10.3390/jmse11091729
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Application of Machine Learning in Storm Surge Problems

Yue Qin,
Changyu Su,
Dongdong Chu
et al.

Abstract: The rise of machine learning (ML) has significantly advanced the field of coastal oceanography. This review aims to examine the existing deficiencies in numerical predictions of storm surges and the effort that has been made to improve the predictive accuracy through the application of ML. The readers are guided through the steps required to implement ML algorithms, from the first step of formulating problems to data collection and determination of input features to model selection, development and evaluation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 143 publications
0
3
0
Order By: Relevance
“…This integration, which may involve techniques like weighted averaging or model ensembling, endows the final meta-model with enhanced generalization capabilities. Meta-modeling achieves a balance between various aspects of the individual models by leveraging their strengths and mitigating their weaknesses, leading to more robust and comprehensive models ( Qin et al, 2023 ). This balance is derived from an in-depth understanding of each model’s performance and characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…This integration, which may involve techniques like weighted averaging or model ensembling, endows the final meta-model with enhanced generalization capabilities. Meta-modeling achieves a balance between various aspects of the individual models by leveraging their strengths and mitigating their weaknesses, leading to more robust and comprehensive models ( Qin et al, 2023 ). This balance is derived from an in-depth understanding of each model’s performance and characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…A thorough and extensive literature review can be found in [1,71], where machine learning models are compared to traditional physically based models.…”
Section: Neural Network Ensemblementioning
confidence: 99%
“…For example, Fan et al [20] developed an artificial neural network-based method for calculating ship-bridge collision forces using numerical simulation data. Qin et al [21] argued that the rise of machine learning has greatly promoted the development of the oceanography field and has used Physics-informed neural networks to address storm surge issues. Kameshwar [22] predicted the collision response of bridge piles based on the response surface methodology.…”
Section: Introductionmentioning
confidence: 99%